2020
DOI: 10.1111/pin.12993
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐MALAT1 regulates proliferation and apoptosis of acute lymphoblastic leukemia cells via miR‐205‐PTK7 pathway

Abstract: Long non-coding RNA (lncRNA) MALAT1 has been confirmed to function as an oncogene in various solid tumors. MALAT1 level has been shown to be upregulated in relapsed acute lymphoblastic leukemia (ALL) patients, but the mechanism is unclear. This study aims to investigate the functional roles and underlying mechanisms of MALAT1 in ALL. MALAT1 and miR-205 expression were assessed by real-time quantitative polymerase chain reaction (RT-qPCR). MTT assay and flow cytometry were performed to evaluate cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, MALAT1 serves as an oncogenic lncRNA in NSCLC proliferation and Gefitinib resistance by acting as a miR-200a sponge ( Feng et al, 2019 ). Consistently, lncRNA MALAT1 also plays a pro-oncogenic role in ovarian cancer ( Jin et al, 2017 ), osteosarcoma ( Zhang et al, 2020 ), acute lymphoblastic leukemia ( Song Y. et al, 2020 ), and colorectal cancer ( Guo et al, 2020 ). Our results showed that IGF2BP2 overexpression increased the MALAT1 level, whereas MALAT1 was significantly downregulated by IGF2BP2 knockdown, suggesting that lncRNA MALAT1 can be regulated by IGF2BP2.…”
Section: Discussionmentioning
confidence: 92%
“…However, MALAT1 serves as an oncogenic lncRNA in NSCLC proliferation and Gefitinib resistance by acting as a miR-200a sponge ( Feng et al, 2019 ). Consistently, lncRNA MALAT1 also plays a pro-oncogenic role in ovarian cancer ( Jin et al, 2017 ), osteosarcoma ( Zhang et al, 2020 ), acute lymphoblastic leukemia ( Song Y. et al, 2020 ), and colorectal cancer ( Guo et al, 2020 ). Our results showed that IGF2BP2 overexpression increased the MALAT1 level, whereas MALAT1 was significantly downregulated by IGF2BP2 knockdown, suggesting that lncRNA MALAT1 can be regulated by IGF2BP2.…”
Section: Discussionmentioning
confidence: 92%
“…Since the concept of lncRNA is just initiated in a short time, in-depth studies of its mechanisms underlying ALL are very limited, and only a few studies have reported several specific lncRNAs that are involved in ALL pathogenesis, such as lncRNA MALAT1, lncRNA VPS9D1-AS1, and lncRNA TEX41 ( 18 , 30 , 31 ). However, few studies on lncRNA have been disclosed in the context of B-ALL chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, MALAT1, a long non-coding RNA (lncRNA) was identified as a regulator of ALL cell proliferation by regulating miR-205. This last has a target in PTK7, a protein tyrosine-kinase [ 116 ]. miR-152 is also regulated by a lncRNA (LINC00221) and presents a role in ALL cell proliferation and apoptosis [ 117 ].…”
Section: Mirnas Involvement In Regulating Periphery B-cellsmentioning
confidence: 99%